Cutaneous Mast Cell Tumor in a Bitch - Gomes, Rafaela Oliveira; Facury, Roberta do Nascimento; Coelho, Mylena Martins; Linhares, Renato Sampaio; Rosado, Isabel Rodrigues; Alves, Endrigo Gabellini Leonel; Martin, Ian (Acta Scientiae Veterinariae, 2022)
Background: The diagnostic of neoplasia in dogs has risen significantly in the last years and this fact is mostly attributed to the longer life expectancy of these animals, which contributes to a greater chance of exposure to carcinogenic agents. In between the diverse tumors that could compromise skin, the mastocytoma is the third most commonly diagnosed neoplasia. It is characterized by being a form of neoplasia with round cells, these being the mast cells. The objective of the present study consisted in relating a case of cutaneous mastocytoma in a 7-year-old bitch mixed-breed treated at the Veterinary Medical Teaching Hospital of the University of Uberaba (UNIUBE) - Uberaba, MG, Brazil. Case: The bitch initially presented a localized nodule external to the right ear pinna with cytology test suggesting a mastocytoma. The nodule was surgically removed and, posteriorly, an histopatholgy was not requested. After 5 months since the emergence of the nodule and a month after its surgical resection, the tutor noticed the presence of a new growth in the ipsilateral cervical region to the previous nodule. At this moment, the responsible veterinarian decided to refer the animal to an oncologist. During the appointment with the oncologist, alterations such as hyporexia and anemia were related, and the presence of a nodule in the right cervical region measuring 4.5 to 4 cm of diameter was verified. Material for cytologic evaluation of the neoplasia was collected and again the result suggested a mastocytoma. The new tumor was also surgically removed but was then referred to histopathological evaluation for diagnostic confirmation, grading and evaluation of surgical margins. The tumor was classified as an infiltrative subcutaneous mastocytoma presenting, additionally, compromised surgical margins. After its excision, the association with a chemotherapy treatment using a protocol of Vimblastina 2 mg/m², i.v. in unique dosage per section, associated with Predinisona 1 mg/kg, v.o, SID was indicated. Each section was realized with an interval of 7 days in between. Only 2 chemotherapy sessions took place. Because of the worsening of the clinical condition associated with a very weakened animal the veterinarian opted for the euthanasia of the animal. Discussion: The diagnostic of mastocytoma must be realized through the association of cytology and histopathology, in case histopathological evaluation is needed to confirm the obtained cytology result, to grade the tumor and to evaluate the compromising of surgical margins. In this sense, it was observed that the bitch was submitted only to cytology diagnostic when it presented the nodule in the ear pavilion. Yet, at the second approach realized by the oncologist, it was possible to realize adequate diagnose methods. However, the animal was not submitted to clinical staging of the mastocytoma due to the non-authorization of the exam by the tutor. Such measure is very important, as it reflects directly in the treatment and prognostic of the animal. Thus, image exams such as abdominal ultrasonography and chest X-ray should have been realized, as well as cytological and histopathological evaluation of the regional lymph nodes, in order to search for metastasis points in these places. As the data suggests, the importance of clinical staging of animals affected by this neoplasia and the importance of cytological evaluation associated with histopathology for a correct diagnosis, prognosis and mastocytoma treatment is noted. It is emphasized that many times veterinarians face impediment related to requesting all necessary exams coming from tutors, which compromises treatment success. Keywords: canine, mast cell, cytology, histopathology, neoplasia, tumor, chemotherapy. Título: Mastocitoma Cutâneo em uma cadela Descritores: canino, mastócito, citologia, histopatologia, neoplasia, tumor, quimioterapia.